Legal Framework of Innovation Activity in the Republic of Serbia - Nikolić, Dušan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Innovations and innovation activity are regulated in the Republic of Serbia by the Law on Innovation Activity, which was fundamentally reformed in 2022 after almost 11 years. For the first time, the terms startup, spinoff, business angel, and other important ones, well-known in the business environment, were introduced into Serbian law. The main goal of the Law on Innovation Activities is to create a national innovation system of the Republic of Serbia and to support the development of innovations. In order to better understand the new legal solutions, it is necessary to answer the questions concerning the broader context: "What is innovation, and what is innovation activity?" The author starts from the broadest theoretical analysis of the basic concepts of innovative activity, then analyzes the Law on Innovation Activity as a whole, and finally provides an overview of the novelties introduced by the adoption of the new Law. The ultimate goal of the analysis is to find the ratio legis of the reformed Law on Innovation Activities.